Two new genera of phorid flies, Macgrathphora and Aurisetiphora, from Costa Rica (Diptera: Phoridae), with recommendations for naming new genera in the family - Brown, Brian V. (Zootaxa, 2022)
Two new genera and four new species of metopinine phorid fly are described from Costa Rica. Macgrathphora new genus is described with the following new species: M. caribbea, M. longifurca, and M. pacifica. In particular, M. caribbea is one of the most abundant phorids collected in a recent inventory project in Northwestern Costa Rica. Aurisetiphora new genus is described for a single species, A. maggiesnowae new species, from a site in the Central Valley, near San José. Guidelines for describing new genera within the Phoridae, especially the Metopininae, are given, and genus Synaptophora Brown is synonymized with Dohrniphora Dahl (new synonymy).